Rare case of gallbladder agenesis presenting with pancreatitis. (8th August 2016) - Thornton, Luke; Goh, Yan Li; Lipton, Mark; Masters, Andrew
Abstract : Gallbladder agenesis (GA) is a rare congenital abnormality with an incidence of 0.01–0.09%. Majority of GA exist alone although it can be associated with other systemic malformations involving the gastrointestinal, genitourinary, cardiovascular and skeletal systems. It is thought that biliary and pancreatic pathologies coexist and this is the second case reported in the literature of GA presenting with pancreatitis.